Analisis Faktor-Faktor yang Memengaruhi Sikap Konsumen dalam Berbelanja Online di Shopee - Alifa Nur Putri Ramadhani; Agus Abdurrahman (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
Increasing the relevance of e-commerce as consumers continue to switch to digital channels. The need to cope with and meet these changes in the market has become a concern for businesses. Identifying the factors that significantly influence online shopping behavior is essential to better understand consumer behavior in this market transition. The purpose of this study was to determine the factors that influence online shopping activities. Quantitative descriptive research method is a type of research applied to this research. The population of this study covers all regions of Indonesia and does not have specific regional characteristics. Purposive sampling is the sampling technique used in this study. The data collection tool used an online questionnaire which was distributed to 150 respondents. The data analysis technique used is statistical analysis, namely multiple linear regression analysis. The results of the analysis show that relative advantage has a positive and significant influence on online shopping attitude. e-WOM has a positive and significant influence on online shopping attitude. Promotion has a positive and significant influence on online shopping attitude. And trust has a positive and significant influence on online shopping attitude. So it can be concluded that relative advantage, e-WOM, promotions, and trust are some of the factors that have an influence on online shopping attitude at Shopee